Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Jasa Aplikasi Gojek Pada Mahasiswa S1 Manajemen Universitas Dharma Andalas - Muhammad Khalbi; Nofri Yendra (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the influence of price and promotion on purchasing decisions for the Gojek app among undergraduate students of Management at Dharma Andalas University. This study used quantitative methods, collecting data through questionnaires distributed to 210 student respondents using a purposive sampling technique. Based on the research results and data analysis using SPSS (Statistical Product and Service Solutions), it was shown that: (1) Price has a positive and significant influence on purchasing decisions, (2) Promotion has a positive and significant influence on purchasing decisions, (3) Price and Promotion have a positive and significant influence on purchasing decisions. Simultaneously, both independent variables have a significant influence on purchasing decisions. These findings indicate that the Gojek app plays a role in shaping consumer preferences through promotion, and price is a primary consideration in purchasing decisions among undergraduate students of Management at Dharma Andalas University, Padang.